MODERNIZATION OF TOURISM INFRASTRUCTURE AND ATTRACTION OF INNOVATIVE INVESTMENTS: A REGIONAL DEVELOPMENT MODEL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The modernization of tourism infrastructure and the attraction of innovative investments play a crucial role in enhancing the economic appeal of regions. The proposed regional development model promotes sustainable growth, improved service quality, and increased competitiveness.